Knowledge, attitude and perception of medical students on COVID-19 vaccines: A study carried out in a Nigerian University - Orok, Edidiong; Ndem, Ekpedeme; Daniel, Eunice (Frontiers in Public Health, 2022)
Objective Vaccine development, distribution, and immunization of large populations have been identified as vital mitigation strategies for curbing the spread of COVID-19. However, vaccine hesitancy is a major barrier to this. The knowledge and perception of COVID-19 vaccines can improve vaccine acceptance. The purpose of this study was to assess medical students' knowledge, attitude, and perception of COVID-19 vaccines. Methods This study was a cross-sectional web-based survey conducted among undergraduate students from the faculties of Basic medical sciences and Clinical sciences, University of Uyo, Akwa Ibom State, Nigeria. The students' knowledge was ranked as excellent (>70%), good (50–69%) and poor (<50%) while perception was categorized into positive (>50%), and negative (<50%). The difference in knowledge based on demographics was analyzed using the Independent sample t-test. The association between demographics, and students' perception was carried out using the Chi-square and Fisher's Exact tests. Analyses were conducted using SPSS software version 25. Results A total of 233 students consented to participate in the study out of which 51.1% were female. Forty-eight students (20.6%) had good knowledge while 41.2% of the participants accepted to take the COVID-19 vaccine. Positive perception was reported among 51.1% (119) of the students. Conclusion There was poor knowledge and positive perception among majority of the students. Educational intervention in form of training should be done to improve medical students' knowledge and perception toward COVID-19 vaccination.